Thermal comfort and grazing behavior of Girolando heifers in integrated crop-livestock (ICL) and crop-livestock-forest (ICLF) systems - Souza, Elaine Coimbra de; Salman, Ana Karina Dias; Cruz, Pedro Gomes da; Veit, Hemerson Maciel; Carvalho, Giovanna Araújo de; Silva, Francyelle Ruana Faria da; Schmitt, Eduardo (Acta Scientiarum. Animal Sciences, 2019)
To compare the integrated crop-livestock-forest (ICLF) and crop-livestock (ICL) systems in relation to thermal comfort and grazing behavior of Girolando heifers, a 2 × 2 crossover trial (two system and two periods) was carried out with eight ¾ Holstein × ¼ Gyr heifers in Xaraés–palisade grass pasture under intermittent stocking with 10 days of occupation period and 20 days of resting. In ICLF, crown cover of eucalyptus planted in rows was 65% at the beginning of the experiment. Animal behavior was assessed through bioacoustics by recording heifers’ sounds for 48 hours. Concomitantly, heifers’ internal temperature (IT,°C) was recorded every 10 min using data logger thermometers adapted to hormone-free intravaginal devices. Air temperature and humidity data were collected by thermohygrometers located in the center of ICLF and ICL for calculating Temperature–Humidity Index (THI). According to THI values, ICLF and ICL did not vary in terms of thermal comfort. However, THI indicated moderate stress (82.26±4.40) during day (06:00 to 17:59h) and mild stress (75.76±4.38) at night (18:00 to 05:59h) in both systems. During day, heifers from ICL had significantly (p < 0.05) higher IT (39.51±0.56oC) than those from ICLF (39.41±0.56oC); the former spent more time grazing and less time drinking water in ICLF (581.35±30.1 and 4.87±1.09 min, respectively) when compared with those from ICL (436.88±28.1 and 10.25±1.09 min, respectively). Therefore, although thermal comfort index did not vary between the systems, under moderate stress, crossbred heifers have lower internal temperatures, resulting in longer diurnal grazing and shorter water drinking time in Eucalyptus-shaded pastures.